Risk of venous thromboembolism with janus kinase inhibitors in inflammatory immune diseases: a systematic review and meta-analysis - Zhang, Juqi; Li, Wenhui; Gong, Mingli; Gu, Yanlun; Zhang, Hanxu; Dong, Bingqi; Guo, Qi; Pang, Xiaocong; Xiang, Qian; He, Xu; Cui, Yimin (Frontiers in Pharmacology, 2023)
Abstract OBJECTIVES To assess the risk of venous thrombosis (VTE) with Janus kinase (JAK) inhibitors in patients with immune-mediated inflammatory diseases. Methods We searched PUBMED, Cochrane and Embase for randomised controlled trials on the incidence of venous thromboembolism with JAK inhibitors in patients with immune-mediated inflammatory diseases. Studies were assessed according to the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines and a meta-analysis was performed. RESULTS A total of 16 studies, involving 18,448 patients, were included in this review. Four approved doses of JAK inhibitors were reported. The meta-analysis showed no significant increase in the risk of VTE in patients treated with JAK inhibitors compared to placebo and TNF inhibitors (RR 0.72, 95% CI (0.33, 1.55); RR 0.94, 95%CI (0.33, 2.69)). Subgroup analysis showed a lower risk of VTE with lower doses of JAK inhibitors. (RR 0.56, 95%CI (0.36, 0.88)). Compared to the higher dose, patients in the tofacitinib group who received the lower dose had a lower risk of pulmonary embolism (RR 0.37, 95%CI (0.18, 0.78)). CONCLUSIONS This meta-analysis of randomised controlled trials (RCTs) showed that patients with IMIDs who received JAK inhibitors had numerically higher but statistically non-significant VTE events compared with patients who received TNF inhibitors and placebo. The risk of pulmonary embolism at high doses of tofacitinib is of concern. These findings help to guide clinical decision-making in the use of JAK inhibitors in patients with IMIDs.